Review of Control Strategies in Lower Extremity Exoskeleton - Devendra Vashist; Rajnish Kumar Sharma (International Journal of Robotics and Automation in Mechanics, 2024)
Personal mobility is one of the biggest challenges for ensuring the quality of rehabilitation in the lives of Persons with Locomotor Disabilities (PwLDs) and old aged persons. In order to ensure effective orthotic rehabilitation, there is need to design and develop more and more automated aids and appliances. In order to know the status of research a study has been made on the controllers of lower limb exoskeleton (LLE). In the present work various application of robotics in lower extremity orthotics were studied and trends reviewed in the advancements in controller technology. The review also analyze assistive orthotic exoskeleton systems catering to the areas of application of the hip, knee and ankle. Another finding of the study on usage application is that fuzzy and PID controllers were mostly-applied to knee areas because of their fine-tuning with area of application. Based on the review, five different categories of control methods were devised. It was found that sliding mode control (SMC) dominated as the most used controller in LLE research. The study provides an overview of the evolving trends in control methods like reinforcement learning, deep neural networks and hybrid control systems. Further the work concludes that there are very few control methods catering specifically to assisting movement of ankle joint.
Keywords: Controllers; Lower Limb Exoskeleton; Orthotics; Rehabilitation devices